The Use of Olive Oil for Reducing the Complaint of Itching Related to Striae Gravidarum in Pregnant Women - Nita Dwi Astikasari; Riza Tsalatsatul Mufida; Shanty Natalia (Universitas Airlangga, 2020)
Introduction: This study is regarding the incidence of complaints of itching made by pregnant women, one of which is caused by striae gravidarum. The purpose of this research was to learn about the use of olive oil to reduce the itching complaints of striae gravidarum among the expectant mothers in the village of Anyer Ponggok Ringin Blitar.Methods: The research design used was True Experimental research. The population examined was the total number of pregnant women in the village of Ringin Anyar, totaling 30 pregnant women. The final respondents totaled 27. The design used was a technical pre-post test control group. The method of sampling used was simple random sampling. The research instrument used was olive oil for 3 days. The research results were then analyzed using the Wilcoxon and Mann-Whitney tests.Results: The results of the analysis showed there to be no difference before or after being given the olive oil to treat the itching of the pregnant women in the village of Ringin Anyar Ponggok Blitar. The prevalence of events in Puskesmas ponggok states that on June 2nd 2016, out of the 28 pregnant women who were examined, 17 of them experienced itching called striae gravidarum.Conclusion: Based on the results of the research, it is expected for all of the expectant mothers to keep their skin moist with olive oil at the beginning of the second trimester in order to reduce the rate of itching in pregnancy.